Pavement markings, design and typical layout details - Friedman, Bruce E. (Synthesis of highway practice (Online), 2006)
TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 356: Pavement Markings--Design and Typical Layout Details identifies variations in pavement marking designs, practices, and policies, as provided by 48 of 50 state departments of transportation, and transportation agencies from the District of Columbia, Puerto Rico and four cities.